Living on the Edge: Social Exclusion and the Receipt of Informal Care in Older People - Lena Dahlberg; Kevin J. McKee (Journal of Aging Research)
Older people have been identified as being at risk of social exclusion. However, despite the fact that care is commonly required in later life and the majority of that care is provided by informal carers, a connection between social exclusion and informal care-receipt has rarely been considered. The aim of this study was to examine how informal care-receipt is related to social exclusion. A face-to-face questionnaire survey on social exclusion and informal care-receipt was carried out among older people (n=1255) living in Barnsley, United Kingdom. Multivariable analyses examined the association between social exclusion and categories of informal care-receipt: care-receiver; assurance-receiver; nonreceiver with no need; and nonreceiver with need. Compared to being a nonreceiver with no need, participants were more likely to be care-receivers or assurance-receivers if they had higher levels of social exclusion. The highest level of social exclusion, however, was found in nonreceivers with need. Despite a lack of informal care and support, formal practical support and personal care were also low in this latter group. Findings are discussed in relation to the conceptualisation of care-receipt and how contact with medical services could be an opportunity for identification and appropriate referral of nonreceivers with need.